Penentuan Permintaan dan Nilai Tambah Produk Industri Kreatif Pada Pasar Lokal - Made Irma Dwiputranti; Andriyani Oktora; Dodi Permadi (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2016)
Recently, creative industries growth significantly. However, this growth is still constrained by various factors, one of which is the funding. This aspect has not been solved well although there has full government support. This is due among other things: 1) there is no form of financing schemes in accordance with the creative industries; 2) the amount of commitments lending by financial institutions is not adequate. 3) have not been socialized and performing well. This constraint requires more detailed analysis of the aspects most and very influential on the growth of the creative industries. This research was conducted through analysis of the logical framework approach as well as industrial cluster approach to the object in the fashion and design , which is well established in Bandung. Outcomes were include: 1) identification of critical success factors (CSF) in small industry based on the demand and the potential of the locality; 2) the mapping capitalization model of stimulus and treatment of the CSF; 3) analysis of products value-added based on demand and market; 4) analysis of capital policy for the creative industry.